Dairy farmers{u2019} cooperative membership, perceptions and choice of marketing channels in Thailand - Thitiya Jitmun; Kuwornu, John K. M.; Datta, Avushek; Anal, Anil Kumar; Ministry of Agriculture and Cooperatives (MOAC), Thailand; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2019)
Since the introduction of modern dairy farming in the early 1960s, the dairy farming sector in Thailand was dominated by dairy cooperatives (DCs). While the growing sector has professionalized, the portion of the milk market share of DCs has reduced significantly, the last decade at an accelerated speed. DCs nowadays contribute only 52% to Thailand{u2019}s milk production and marketing compared with 63% in 2007. This implies that DCs face intense competition from alternative marketing channels like private organizations (POs). The growing milk collecting business has attracted private investors that resulted in the creation of POs in the dairy industry. The objectives of this study were threefold as follows: (a) to examine the factors influencing farmers{u2019} membership of DCs, (b) to assess the dairy farmers{u2019} perceptions of the milk collecting centers (MCCs) regarding the milk marketing of their members, and (c) to examine the factors influencing farmers{u2019} choice of milk marketing channels. The study was conducted in Provinces of Central (Saraburi and Lop Buri) and Northeastern (Nakhon Ratchasima) Regions of Thailand. These three Provinces were selected as they represent the top three milk production areas in Thailand regarding the population of dairy farmers and dairy cattle. Additionally, these regions host a variety of farm types and operating scales produced within a highly competitive environment among DCs and POs, which are more appropriate for this study. Primary data were gathered from respondents through face-to-face interviews using questionnaire administration. Two types of farmers were surveyed: members of DCs and members of POs representing the two key marketing channels. In total, 385 dairy farmers consisting of 159 DCs members and 226 POs members were selected. This study employed the binary logit regression model to examine the factors influencing farmers{u2019} membership of DCs; weighted average index (WAI) to investigate farmers{u2019} perceptions of MCCs with regard to the milk marketing of their members; and binary probit regression model to examine the factors influencing farmers{u2019} choice of milk marketing channels. The results of the binary logit regression analysis revealed that age, educational level, dairy farming experience, herd size, distance to the MCCs, milk price, training and education service access, and farm input service access positively influenced the farmers{u2019} decision to be DCs members, whereas the square of the herd size and monthly payment period negatively influenced the farmers{u2019} membership of DCs. The results of the WAI analysis showed that there were similar perceptions about the role of MCCs between the two groups of farmers regarding the basic needs of dairy farmers, but with a stronger focus of economic issues for POs members, whereas the views of DCs member were more from the perspective of ownership. The farmers were somewhat satisfied with their MCCs{u2019} performance, except that POs farmers were less satisfied with credit services. The results of the binary probit regression analysis showed that dairy farming experience, the number of years of membership of the MCCs, distance to the MCCs, milk price, payment period, access to market information, advisory services, credit services, and farm input services had a positive influence on the choice of DCs as the marketing channel, whereas marketing experience had a negative influence.The results of this research have implications for milk marketing by dairy farmers in Thailand.
A Dissertation submitted in partial fulfillment of the requirements for the Degree of Doctor of Philosophy in AgriBusiness Management
Thesis (Ph.D.) - Asian Institute of Technology, 2019
Keywords: Dairying, Cooperative -- Thailand; Marketing channels -- Thailand; Milk trade -- Thailand